Clinical and Surgical Evaluations of Reoperation After Mechanical Mitral Valve Replacement Due to Different Etiologies - Li, Jiehui; Wang, Shuiyun; Sun, Hansong; Xu, Jianping; Dong, Chao; Song, Min; Yu, Qibin (Frontiers in Cardiovascular Medicine, 2022)
Background: This study aimed to evaluate the clinical and surgical characteristics of patients who required reoperation after mechanical mitral valve replacement (MVR). Methods: We retrospectively identified 204 consecutive patients who underwent reoperation after mechanical MVR between 2009 and 2018. Patients were categorized according the reason for reoperation (perivalvular leakage, thrombus formation, or pannus formation). The patients' medical and surgical records were studied carefully and the rates of in-hospital complications were calculated. Results: The mean age was 51±12 years and 44% of the patients were male. The reasons for reoperation were perivalvular leakage (117 patients), thrombus formation (35 patients), and pannus formation (52 patients). The most common positions for perivalvular leakage were at the 6–10 o'clock positions (proportions of ≥25% for each hour position). Most patients had an interval of >10 years between the original MVR and reoperation. The most common reoperation procedure was re-do MVR (157 patients), and 155 of these patients underwent concomitant cardiac procedures. There were 10 in-hospital deaths and 32 patients experienced complications. The 10-year survival rate was 82.2 ± 3.9% in general, and the group of lowest rate was patients with PVL (77.5 ± 5.2%). The independent risk factors were “male” (4.62, 95% CI 1.57–13.58, P = 0.005) and “Hb <9g/dL before redo MV operation” (3.45, 95% CI 1.13–10.49, P = 0.029). Conclusion: Perivalvular leakage was the most common reason for reoperation after mechanical MVR, with a low survival rate in long term follow-up relatively.